INCREASE THE ROLE OF THE FAMILY OF NUTRITION NEEDS TO IMPROVE IMMUNITY FOR THE PANDEMIC COVID-19 IN BULUAMPAL BENDO PARE KEDIRI - Nurul Laili; Ayu Septianingrum; Surya Pramesti Regita Cahyani; Yahya Iman Nurcholis; Anindya Syaza Ni’matul Azizah (Universitas Airlangga, 2021)
Introduction: Covid-19 is a virus that attacks the human immune system. The severity is influenced by endurance, age and pre-existing disease (comorbid). Treatment is given to relieve symptoms and increase endurance. Individual conditions require immunity or immunity to fight the virus. Immunity can be formed through nutritional intake or balanced nutrition during the Covid-19 pandemic. The general objective of this community service activity is that health workers and students are able to increase community and family awareness to prevent Covid-19 transmission through increasing immunity by meeting nutritional needs.Methods: Activities in community service programs by conducting education or counseling as well as demonstrations of correct food processing and selection of food ingredients and samples that are easy to find and obtain in the environment in Buluampal Hamlet, Bendo Village, Pare District.Results: Families who participate in educational or outreach and demonstration activities can understand food that can be consumed during the pandemic, correct food processing, understanding of the content or composition of balanced nutrition and traditional food ingredients that can be used as an immune booster during a pandemic. The post-test results on family and community knowledge show that most of the families 77.78% understand about meeting nutritional needs during a pandemic including food / balanced nutrition for family members.Conclusion: Community service activities can increase understanding and knowledge of balanced nutrition to increase immunity during a pandemic and know how to process food ingredients and use home yards for herbal plants that can increase immunity.